BASICS OF RADIATION DIAGNOSTICS OF THE LUNG IN CHILDREN - Ахмедов Я. А.; Шодикулова П. Ш; Бахриева Д. Ш. (Web of Journals Publishing, 2024)
Radiation diagnostics of the lungs in children has its own characteristics. These features depend both on the technical aspects of radiation examination and on the anatomical structure of the child's respiratory system. In modern pediatrics, among a large number of various methods, the diagnosis of radiation methods is very important and often dominant. Therefore, the pediatrician should be well acquainted with the basics of radiation diagnostics of the lungs in children and the latest advances in it.
Keywords: Radiation imaging methods, X-ray methods, X-ray anatomy, X-ray physiology, semiotics of diseases.